Appendicitis inflammatory response score: a novel scoring system for acute appendicitis - Patil, Suresh; Harwal, Rahul; Harwal, Sharanabasappa; Kamthane, Sangamesh (International Surgery Journal, 2017)
Background: Acute appendicitis is one of the most common surgical emergencies encountered by doctors on call with emergency appendicectomy being a very common outcome of emergency laparotomies. There's been a marked decline in mortality over the past 50 years, but the rates of perforation and negative laparotomy have not changed much as they're influenced by factors untouched by technological advances. Methods: A prospective comparative study to compare appendicitis inflammatory response score (AIR) and Alvarado scoring systems in evaluating suspected cases of acute appendicitis. 100 patients presenting with pain in the right lower quadrant of abdomen at the surgical clinics at Basaveshwar Teaching and General Hospital, Kalaburagi, Karnataka, India, who after clinical examination and relevant investigations were provisionally diagnosed to have acute appendicitis and warranted surgery for the same were evaluated using the scoring systems - Alvarado Score and Appendicitis Inflammatory Response Score. The scores were tallied and compared with final histopathology report. The study was conducted for a period of one and a half year. Results: The results revealed that AIR (at score >4) demonstrated a higher sensitivity and specificity compared to Alvarado score (89.9 versus 78.6%) and (63.6 versus 54.5) respectively. Alvarado showed a slightly better sensitivity at score>8 (21.3 versus 12.3%). Conclusions: The Appendicitis Inflammatory Response Score outperformed the Alvarado score. It holds promise to be incorporated into the clinician's daily inventory in efficiently diagnosing Appendicitis.